1986
DOI: 10.1111/j.1365-2125.1986.tb05247.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative assessment of caffeine partial clearances in man.

Abstract: Five subjects who participated in an earlier study (Lelo et al., 1986b) of the comparative pharmacokinetics of caffeine (CA) and its primary monodemethylated metabolites paraxanthine (PX), theobromine (TB) and theophylline (TP) were administered CA to steady-state. Using areas under the plasma concentration-time curves for each of the dimethylxanthines derived from CA in the steady-state study and individual plasma clearances of PX, TB and TP determined in the previous study, the fractional conversion of CA to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0
5

Year Published

1989
1989
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(63 citation statements)
references
References 11 publications
2
55
0
5
Order By: Relevance
“…Corresponding values for paraxanthine were 4.1% and 4.1%. Parax-'Copies of the SSQ may be obtained from Jack E. James. anthine was measured because (a) it is the principal metabolic product of caffeine (Lelo et al, 1986b), (b) it correlates better with observed caffeine intake than other major demethylated metabolites (theobromine, theophylline) (Lelo et al, 1986a), and (c) it has been found to produce slightly better correlations with diary records than those produced by plasma caffeine . The last of these findings is consistent with evidence concerning the pharmacokinetics of caffeine and paraxanthine.…”
Section: Saliva Assaysmentioning
confidence: 99%
“…Corresponding values for paraxanthine were 4.1% and 4.1%. Parax-'Copies of the SSQ may be obtained from Jack E. James. anthine was measured because (a) it is the principal metabolic product of caffeine (Lelo et al, 1986b), (b) it correlates better with observed caffeine intake than other major demethylated metabolites (theobromine, theophylline) (Lelo et al, 1986a), and (c) it has been found to produce slightly better correlations with diary records than those produced by plasma caffeine . The last of these findings is consistent with evidence concerning the pharmacokinetics of caffeine and paraxanthine.…”
Section: Saliva Assaysmentioning
confidence: 99%
“…Both 1MX and 3-methylxanthine (3MX) are formed as References primary metabolites from theophylline but only 1MX is thine [5] which is demethylated further to 1MX and …”
Section: Discussionmentioning
confidence: 99%
“…procedure of Lelo et al [7]. Plasma allopurinol and oxypurinol concentrations were similarly measured by h.p.l.c.…”
Section: Analyticalmentioning
confidence: 99%
See 1 more Smart Citation
“…Through these literature searches the applicant identified a total of 37 publications as being pertinent to the health claim: 10 human intervention studies (Kuznicki and Turner, 1986;Lieberman et al, 1987a;Griffiths et al, 1990;Silverman and Griffiths, 1992;Mumford et al, 1994;Smith et al, 1999;Smit and Rogers, 2000;Van Dongen et al, 2001;Wyatt et al, 2004;Smith, 2009), 15 human studies on bioavailability or mechanistic studies (Marks and Kelly, 1973;Newton et al, 1981;Bonati et al, 1982;Blanchard and Sawers, 1983;Lelo et al, 1986;Nehlig et al, 1992;Liguori et al, 1997;Fredholm et al, 1999;Magkos and Kavouras, 2005;Specterman et al, 2005;Seng et al, 2009Seng et al, , 2010Arnaud, 2011;Perera et al, 2011;Smith et al, 2013), and 12 non-human studies (Bunker and McWilliams, 1979;Arnaud, 1985;Schiffmann et al, 1991;Okada et al, 1996;Ledent et al, 1997;Wang and Lau, 1998;El Yacoubi et al, 2000;Fredholm et al, 2001;Yamato et al, 2002;Liu and Gao, 2007;Costa et al, 2008;Botton et al, 2010). The applicant also provided four human intervention studies (Rogers, 2011, unpublished;Smith et al, 2011, unpublished;Kennedy, 2011...…”
Section: Scientific Substantiation Of the Claimed Effectmentioning
confidence: 99%